2010
DOI: 10.1002/elan.201000100
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Behavior of Telmisartan and Cathodic Adsorptive Stripping Voltammetric Method for Its Assay in Pharmaceutical Dosage Forms and Biological Fluids

Abstract: Electrochemical behavior of Telmisartan and optimum conditions for its assay were investigated by using cyclic voltammetry and square-wave voltammetry. All studies were based on the quasi-reversible and adsorption-controlled electrochemical reduction signal of TS at about À1.50 V versus Ag/AgCl at pH 10.0 in Britton-Robinson buffer. The peak current was found to change linearly with concentration from 1.69 nM (0.87 mg/L) to 27.5 nM (14.15 mg/ L). The limit of detection and the limit of quantification were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…Result of concentration studies showed that an average peak current of reduction wave changed linearly with RPN concentration in the range from 1.5 to 150 nmol l -1 by obeying the calibration equation I p (nA) = 0.51[RPN] (nmol l -1 ) + 10.65 with R 2 = 0.9992. Value of R 2 is the evidence of good linearity between peak current and concentration of RPN (Table I) Limits of detection and quantitation: Limit of detection (LOD) and limit of quantitation (LOQ) values for RPN were calculated using the relations LOD = 3s/m and LOQ = 10s/m 23,24 . The abbreviation of s is the standard deviation of intercept of calibration curve and m is the slope of the related calibration curve, LOD and LOQ values were found 5.18 nmol l -1 (2.12 µg l -1 ) and 17.25 nmol l -1 (7.07 µg l -1 ), respectively.…”
Section: Methods Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Result of concentration studies showed that an average peak current of reduction wave changed linearly with RPN concentration in the range from 1.5 to 150 nmol l -1 by obeying the calibration equation I p (nA) = 0.51[RPN] (nmol l -1 ) + 10.65 with R 2 = 0.9992. Value of R 2 is the evidence of good linearity between peak current and concentration of RPN (Table I) Limits of detection and quantitation: Limit of detection (LOD) and limit of quantitation (LOQ) values for RPN were calculated using the relations LOD = 3s/m and LOQ = 10s/m 23,24 . The abbreviation of s is the standard deviation of intercept of calibration curve and m is the slope of the related calibration curve, LOD and LOQ values were found 5.18 nmol l -1 (2.12 µg l -1 ) and 17.25 nmol l -1 (7.07 µg l -1 ), respectively.…”
Section: Methods Validationmentioning
confidence: 99%
“…Its remarkable sensitivity is attributed to the combination of an effective accumulation step with an advanced measurement procedures that generates an extremely favorable signal to back ground ratio. It usually involves a simple deposition step and most of the excipients used, not interfere in the subsequent determination of the drugs and there are many applications of stripping voltammetric methods [17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%
“…The advance in experimental electrochemical techniques in the field of analysis of drugs is due to their simplicity, low cost, and relatively short analysis time as compared with the other techniques. However, since most drugs are less active electrochemically, little attention has been paid so far to the use of electrochemical detection methods [40][41][42][43].…”
Section: Electrochemical Methods Of Analysismentioning
confidence: 99%
“…Tasemir et al [40] investigated the electrochemical behavior of Telmisartan and optimum conditions for its assay by using cyclic voltammetry and square-wave voltammetry. They based all studies on the quasi-reversible and adsorption-controlled electrochemical reduction signal of TS at about À1.50 V versus Ag/AgCl at pH 10.0 in Britton-Robinson buffer.…”
Section: Voltammetrymentioning
confidence: 99%
“…Literature survey reveals that difference in spectrophotometry 5 , spectrophotometry in combination with other drugs [6][7][8][9][10] , colorimetry [11][12] , immunoassay development 13 , liquid chromatographytandem mass spectrometry [14][15][16][17][18] , HPLC [19][20][21][22][23][24][25] , micellar electrokinetic chromatographic method 26 , linear sweep polarography 27 , determination of pKa 28 , capillary zone electrophoresis 29 , HPTLC [30][31][32][33] , voltametry 34 are reported for estimation of telmisartan.…”
Section: Introductionmentioning
confidence: 99%